2021
DOI: 10.3390/su131810079
|View full text |Cite
|
Sign up to set email alerts
|

Soils and Beyond: Optimizing Sustainability Opportunities for Biochar

Abstract: Biochar is most commonly considered for its use as a soil amendment, where it has gained attention for its potential to improve agricultural production and soil health. Twenty years of near exponential growth in investigation has demonstrated that biochar does not consistently deliver these benefits, due to variables in biochar, soil, climate, and cropping systems. While biochar can provide agronomic improvements in marginal soils, it is less likely to do so in temperate climates and fertile soils. Here, bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 184 publications
0
7
0
Order By: Relevance
“…Improving the use of dairy-derived bioproducts as soil amendments requires studies that will elucidate the mechanisms controlling P chemistry and availability in soils (Ajiboye et al, 2007;Peak et al, 2012;Gelardi and Parikh, 2021). In this paper, research showed that the majority of P in the amended soils was either absorbed P or Ca-P species such as hydroxyapatite.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Improving the use of dairy-derived bioproducts as soil amendments requires studies that will elucidate the mechanisms controlling P chemistry and availability in soils (Ajiboye et al, 2007;Peak et al, 2012;Gelardi and Parikh, 2021). In this paper, research showed that the majority of P in the amended soils was either absorbed P or Ca-P species such as hydroxyapatite.…”
Section: Discussionmentioning
confidence: 97%
“…If biochar is modified to maximize removal of phosphate from wastewater using Fe-modification, the final product could be a beneficial slow-release P source that could supply P to plants and limit its leaching into surface and ground waters (Yao et al, 2013;An et al, 2021;Wang et al, 2022). Several recent reviews have indicated the need for availability studies and speciation studies to better understand the mechanisms controlling P uptake and release from biochar so that it can be effectively used as a sustainable P fertilizer source (Kopecky et al, 2020;Zhang et al, 2020;Gelardi and Parikh, 2021). Thus, the goal of this project was to investigate P species and availability in calcareous soils amended with various forms of dairy-derived nutrients and biochar in a barley (Hordeum vulgare L.) greenhouse growth trial.…”
Section: Introductionmentioning
confidence: 99%
“…The result reveals that the highest mean collar diameter was recorded under topsoil + biochar treatment. Biochar can increase growth of plants in some circumstances such as in collar diameter and is more effective in giving desire plant performance unlike other larger amount of compost and fertilizer [27]. Agegnehu et al…”
Section: Discussionmentioning
confidence: 99%
“…Large-scale biochar production may compete with land used for food crops or natural habitats, causing ethical concerns when it leads to land-use changes that negatively impact food security, biodiversity, or local communities' livelihoods. There are knowledge gaps regarding the long-term effects of biochar on soil, ecosystems, and human health, necessitating ongoing research to assess the true impact of biochar utilization [55].…”
Section: Environmental and Ethical Concerns Related To Biochar Produc...mentioning
confidence: 99%